Effects of Increasing Histidine:Lysine Ratio During Lactation on Sow and Litter Performance - Abigail K. Jenkins; Mikayla S. Spinler; Jason C. Woodworth; Jordan T. Gebhardt; Robert D. Goodband; Mike D. Tokach; Joel M. DeRouchey; Keith D. Haydon (Kansas Agricultural Experiment Station Research Reports, 2024)
A total of 88 sows (Line 241, DNA) and their offspring were used to evaluate the effect of increasing SID His:Lys ratio in lactating sow diets on sow and litter performance. Sows were blocked by parity and body weight (BW) on approximately d 110 of gestation and allotted to one of three dietary treatments of increasing SID His:Lys ratios (40, 50, or 60% of Lys). Sows were fed approximately 6 lb/d of their treatment diet from d 110 of gestation until farrowing, after which they were allowed ad libitum access to their treatment diet. Litters were cross fostered within 48 h after farrowing to equalize litter size. Increasing SID His:Lys ratio did not affect (P > 0.10) sow BW, backfat, caliper score, or loin depth on d 110 of gestation or at weaning and did not alter the change in those measurements over the lactation period. Total born did not statistically differ (P < 0.10) based on sow lactation diet, however, there were numerical differences between treatments. Increasing SID His:Lys ratio tended to increase and then decrease (quadratic, P ≤ 0.062) d 7 and weaning litter weight with sows fed a SID His:Lys ratio of 50% having the greatest litter weight. Increasing SID His:Lys ratio tended to increase d 7 to wean piglet ADG (linear, P = 0.100) but did not impact litter ADG or pre-weaning mortality (P > 0.10). Increasing SID His:Lys ratio increased and then decreased (quadratic, P = 0.027) total milk yield from d 2 of lactation until weaning and tended to increase and then decrease average daily milk yield (quadratic, P = 0.078) with sows fed a SID His:Lys ratio of 50% having the greatest total and average daily milk yield. Increasing SID His:Lys ratio (P > 0.10) did not affect milk composition. These results suggest that increasing the SID His:Lys ratio to 50% tended to increase litter weight on d 7 and at weaning and average daily milk yield.
Keywords: histidine; lactating sow; litter performance